Determinasi Energi Metabolis dan Kandungan Nutrisi Hasil Samping Pasar Sebagai Potensi Bahan Pakan Lokal Ternak Unggas - Sugiyono Sugiyono; Novita Hindratiningrum; Yuni Primandini (Agricultural Faculty, 2015)
(Determination of metabolic energy and nutrient market by product for local poultry feed ingredients)ABSTRACT. This study aims to examine the metabolic energy (ME) and proximate analysis of the coconut husk, garlic skin, heart of young jackfruit, in order to see its potential as a local feed ingredients for poultry, especially chicken. The study was conducted in 3 stages include feed preparation stage, treatment stage and retrieval of data. Stage of treatment involves measurement of metabolic energy to